(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Herbal mixtures are widely used in Ugep, Cross River State, Nigeria, for their perceived therapeutic benefits, yet concerns persist regarding their safety and efficacy due to limited regulation. This study evaluated the bioactive compounds and microbiological profiles of ten commonly marketed herbal mixtures using primary data collection methods. Samples were procured from local markets, and phytochemical screening identified bioactive compounds such as alkaloids, flavonoids, tannins, and saponins. Microbial analysis assessed contamination levels using standard plate count techniques, revealing the presence of pathogens like Escherichia coli, Staphylococcus aureus, and Salmonella spp. in varying concentrations. Results showed that 70% of samples contained flavonoids and tannins, while 40% exceeded the World Health Organization (WHO) microbial limit of 10⁵ CFU/g for aerobic bacteria. The highest microbial load was 2.3 × 10⁶ CFU/g, indicating significant contamination risks. Theoretical insights from the Biogenic Theory framed the study, emphasizing the natural origin of bioactive compounds and their potential health impacts when compromised by microbial contamination. These findings align with recent literature highlighting variability in herbal product quality across Nigeria. Poor hygiene during preparation and storage likely contributed to contamination, underscoring the need for stricter quality control. Recommendations include enforcing regulatory standards, improving production hygiene, and educating vendors on safe handling practices. This study provides critical data for stakeholders aiming to enhance the safety and efficacy of herbal mixtures in Ugep.